2010
DOI: 10.1002/micr.20736
|View full text |Cite
|
Sign up to set email alerts
|

Complete free flap loss due to extensive hemodilution

Abstract: We demonstrate the clinical relevance of extensive intraoperative hyperhydration, which can provoke a complete free flap loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 17 publications
0
23
0
1
Order By: Relevance
“…However, the study was limited by a very small sample size. Another retrospective study, by Namdar et al, found a significant association between saline infusion volumes and flap loss, as well as total infusion volume to body weight ratios and flap loss . Again, they were limited by a sample size of 48, with only four flap losses.…”
Section: Discussionmentioning
confidence: 97%
“…However, the study was limited by a very small sample size. Another retrospective study, by Namdar et al, found a significant association between saline infusion volumes and flap loss, as well as total infusion volume to body weight ratios and flap loss . Again, they were limited by a sample size of 48, with only four flap losses.…”
Section: Discussionmentioning
confidence: 97%
“…24 In contrast, a study by Namdar et al found a significant association between saline infusion volumes and flap loss, as well as total infusion volume to body weight ratios and flap loss. 46 Again, they were limited by a sample size of 48, with only four flap losses. In a retrospective review of 354 breast free flaps, Zhong et al observed an increased rate of perioperative complications in patients with increased rates of fluid resuscitation.…”
Section: Discussionmentioning
confidence: 99%
“…These include employment of systemic medications such as Heparin (intravenously and PTT-controlled or as subcutaneous injections), HES, Albumine, and techniques of haemodilution using different concentrations of saline infusions. Especially the effect of haemodilution has been reported contradictory with groups describing a significant increase in flap loss [34][35][36][37][38][39]. As one of the more recent approaches, Sildenafil (Viagra V R ) has been shown to postoperatively increase the bloodflow in free LD transfers in one experimental animal study [40].…”
Section: Discussionmentioning
confidence: 99%